Visual attractiveness is leaky: the asymmetrical relationship between face and hair - Saegusa, Chihiro; Intoy, Janis; Shimojo, Shinsuke (Frontiers in Psychology, 2015)
Predicting personality is crucial when communicating with people. It has been revealed that the perceived attractiveness or beauty of the face is a cue. As shown in the well-known “what is beautiful is good” stereotype, perceived attractiveness is often associated with desirable personality. Although such research on attractiveness used mainly the face isolated from other body parts, the face is not always seen in isolation in the real world. Rather, it is surrounded by one’s hairstyle, and is perceived as a part of total presence. In human vision, perceptual organization/integration occurs mostly in a bottom up, task-irrelevant fashion. This raises an intriguing possibility that task-irrelevant stimulus that is perceptually integrated with a target may influence our affective evaluation. In such a case, there should be a mutual influence between attractiveness perception of the face and surrounding hair, since they are assumed to share strong and unique perceptual organization. In the current study, we examined the influence of a task-irrelevant stimulus on our attractiveness evaluation, using face and hair as stimuli. The results revealed asymmetrical influences in the evaluation of one while ignoring the other. When hair was task-irrelevant, it still affected attractiveness of the face, but only if the hair itself had never been evaluated by the same evaluator. On the other hand, the face affected the hair regardless of whether the face itself was evaluated before. This has intriguing implications on the asymmetry between face and hair, and perceptual integration between them in general. Together with data from a post-hoc questionnaire, it is suggested that both implicit non-selective and explicit selective processes contribute to attractiveness evaluation. The findings provide an understanding of attractiveness perception in real-life situations, as well as a new paradigm to reveal unknown implicit aspects of information integration for emotional judgment.